A simulation study on the temperature-dependent release of endocrine-disrupting chemicals from polypropylene and polystyrene containers - Tooraj Massahi; Abdullah Khalid Omer; Amir Kiani; Borhan Mansouri; Hamed Soleimani; Nazir Fattahi; Masoud Moradi; Kiomars Sharafi (Scientific Reports)
Abstract Due to the ubiquity of plastic packaging, this study evaluated the release of endocrine-disrupting chemicals (EDCs) into liquid foods at various temperatures. Solid-phase extraction (SPE) and gas chromatography-mass spectrometry (GC/MS) methods were used to identify EDCs, including phthalates (BBP, DEHP, DBP), bisphenol A (BPA), and nonylphenol (NP) from cups and containers made of polypropylene (PP) and general-purpose polystyrene (GPPS). The distilled water in PP and GPPS contained no EDCs at 4–10 °C. DEHP, DBP, BBP, BPA, and NP were found in water contained in PP cups and containers at higher temperatures (40–100 °C), with DEHP released the most at 100 °C (1242.5 ± 53.0 ng/L and 1615.3 ± 68.9 ng/L) for water contained in cups and containers, respectively. No BPA, DBP, or BBP was found in the contents of GPPS cups or containers at any temperature. The average EDCs released from PP cups and containers at every storage temperature was significantly higher (P < 0.001) than GPPS. These findings highlight the importance of temperatures and material composition in plastic packaging for food safety. Consumers should be careful when using plastic cups and containers, especially at higher temperatures, as EDC release can pose health risks.